Hubungan Antara Daya Terima Makanan Dengan Tingkat Kepuasan Pelayanan Gizi Pasien Hipertensi Rawat Inap Di RSUP Dr Soeradji Tirtonegoro Klaten - Agustina, Fika; , Ibu Endang Nur W, SST, M.Si Med; , Ibu Ririn Yuliati S. ST., M.Si (2016)
Introduction: Food service in the hospital is one of important parts of patient care, food service will affect the food acceptance, and the statisfaction patients levels of nutrition services. Objective: This study aimed to determine the relationship between food acceptance satisfaction levels of nutrition services on patients with hypertension at dr Soeradji Tirtonegoro Hospital Klaten. Research method: This research design was observational with cross sectional approach. Respondents were patient whit hypertension who were hospitalized at dr. Soeradji Tirtonegoro Hospital Klaten. Sampling method using consecutive sampling. Food acceptance and nutrition services satisfaction levels obtained by questionnaire. Test that used to determine the relationship between food acceptance and satisfaction levels of nutrition services was Spearman's rank correlation test. Results: The univariate results show that 93.3% of patients liked the appearance of the food, 100% of patients liked the taste of food, 96.7% of patients said that the food services was good, 90% of patients said that cutlery was clean, 86.7% of patients liked the over all of food acceptance and 96.7% of patients were satisty with the nutrition services. The bivariate results indicated that there was no relationship between food appearance, taste the food, the overall acceptability of food with satisfaction levels of nutrition services on hypertensive patients at dr. Soeradji Tirtonegoro Hospital Klaten. Conclusion : There was no relationship between the food appearance, taste of the food, the overall acceptability of food with the satisfaction levels of nutrition services on hospitalized hypertensive patients at melati 2 room dr Soeradji Tirtonegoro Hospital Klaten. There was a relationship beetwen food service, and the cleanliness of cultery with the satisfaction levels of nutrition services on hospitalized hypertensive patients at melati 2 room dr Soeradji Tirtonegoro Hospital Klaten. Suggestion: If needs further studies to all patients with hypertension to determine the acceptability of food and the level of satisfaction.